IMPLEMENTATION OF THE RUP METHOD ON THE LABUHAN BATU UNIVERSITY STUDENT ACTIVITY UNIT INFORMATION SYSTEM - Siti Aisah Siregar; Deci Irmayani; Muhammad Halmi Dar (Sean Institute, 2021)
The Student Activity Unit (UKM) is a place where students who have the same interests and hobbies gather in a university. Univ. Labuhan Batu is a private university in Rantau Prapat which has 5 SMEs, at the time of registration, prospective SME members visit the UKM booths that have been opened by UKM management, besides that there are several other obstacles such as UKM Univ. Labuhan Batu is recorded manually only from the Student side of the Univ. Labuhan Batu, which contains the name of the PIC, date of activity, number, name of SME, place, start, finish, a number of attendance, meeting to, information, also material data that is not neatly arranged, as well as monthly report collection. In order to support the recording of activities in terms of attendance, members, and materials taught to the registration of SME members, the researchers created a web-based SME information system using the Rational Unified Process method, in this study using black-box testing. RUP is a method that uses the concept of object-oriented and has activities that focus on model development using the Unified Modeling Language (UML). The result of this research is an information system that can be used by SMEs, SME members, and the student body of Univ. Labuhan Batu makes it easy to collect attendance information, member data, activity data, materials, and announcements. and has activities that focus on model development using the Unified Modeling Language (UML). The result of this research is an information system that can be used by SMEs, SME members, and the student body of Univ. Labuhan Batu makes it easy to collect attendance information, member data, activity data, materials, and announcements. and has activities that focus on model development using the Unified Modeling Language (UML). The result of this research is an information system that can be used by SMEs, SME members, and the student body of Univ. Labuhan Batu makes it easy to collect attendance information, member data, activity data, materials, and announcements.